An Anti‐Biofouling Flexible Fiber Biofuel Cell Working in the Brain. Issue 5 (23rd March 2022) - Guo, Yue; Chen, Chuanrui; Feng, Jianyou; Wang, Liyuan; Wang, Jiajia; Tang, Chengqiang; Sun, Xuemei; Peng, Huisheng
Abstract: Biofuel cell (BFC) that transfers chemical energy into electricity is a promising candidate as an energy‐harvesting device for implantable electronics. However, there still remain major challenges for implantable BFCs, including bulky and rigid device structure mismatching with soft tissues such as the brain, and the power output decreases due to the fouling process in a biological environment. Here, a flexible and anti‐biofouling fiber BFC working in the brain chronically is developed. The fiber BFC is based on a carbon nanotube fiber electrode to possess small size and flexibility. A hydrophilic zwitterionic anti‐biofouling polydopamine‐2‐methacryloyloxyethyl phosphorylcholine layer is designed on the surface of fiber BFC to resist the nonspecific protein adsorption in a complex biological environment. After implantation, the fiber BFC can achieve a stable device/tissue interface, along with a negligible immune response. The fiber BFC has first realized power generation in the mouse brain for over a month, exhibiting its promising prospect as an energy‐harvesting device in vivo. Abstract : A flexible and anti‐biofouling fiber biofuel cell is designed from carbon nanotube fiber electrode and hydrophilic zwitterionic anti‐biofouling polymer layer towards implantable applications in soft tissues. After being implanted in the mouse brain as a promising energy harvesting device, it shows high power density retention and can work over one month.